Electronic medical record acceptance using technology acceptance model at Panti Waluyo Hospital Surakarta - Safitri, Rizky Nur; Widiyanto, Wahyu Wijaya (Science Midwifery, 2025)
The adoption of Electronic Medical Records (EMR) in Indonesia has been accelerated by national regulations; however, many hospitals continue to face significant challenges such as limited infrastructure, varying levels of digital literacy among healthcare workers, and resistance to shifting from paper-based systems. These issues highlight the urgency of evaluating user acceptance in specific hospital contexts. This study evaluates the acceptance of EMR implementation at Panti Waluyo Hospital Surakarta using the Technology Acceptance Model (TAM). A descriptive qualitative design was applied through in-depth interviews, observations, and document reviews. Fifteen participants, including physicians, nurses, medical record officers, and administrative staff, were purposively selected to represent core EMR user groups. The findings indicated that 73% of respondents perceived EMR as useful in improving documentation efficiency and accuracy, while 67% agreed that the system was easy to navigate. Moreover, 80% expressed willingness to continue using EMR. Barriers identified included technical disruptions (40%) and the need for continuous training (53%). Overall, the results suggest that EMR adoption is positively accepted within the hospital, although organizational support and infrastructure improvements remain necessary. The study concludes that perceived usefulness and perceived ease of use play significant roles in shaping user attitudes and behavioral intentions, which in turn influence actual system use. Strengthening user competence, addressing digital literacy gaps, and ensuring technical reliability are essential to sustain EMR implementation in healthcare settings.